Virulence Genes of S. aureus from Dairy Cow Mastitis and Contagiousness Risk - Magro, Giada (Toxins (Basel), 2017)
Staphylococcus aureus (S. aureus) is a major agent of dairy cow intramammary infections: the different prevalences of mastitis reported might be related to a combination of S. aureus virulence factors beyond host factors. The present study considered 169 isolates from different Italian dairy herds that were classified into four groups based on the prevalence of S. aureus infection at the first testing: low prevalence (LP), medium–low (MLP), medium–high (MHP) and high (HP). We aimed to correlate the presence of virulence genes with the prevalence of intramammary infections in order to develop new strategies for the control of S. aureus mastitis. Microarray data were statistically evaluated using binary logistic regression and correspondence analysis to screen the risk factors and the relationship between prevalence group and gene. The analysis showed: (1) 24 genes at significant risk of being detected in all the herds with infection prevalence >5%, including genes belonging to microbial surface components recognizing adhesive matrix molecules (MSCRAMMs), immune evasion and serine proteases; and (2) a significant correlation coefficient between the genes interacting with the host immune response and HP isolates against LP ones. These results support the hypothesis that virulence factors, in addition to cow management, could be related to strain contagiousness, offering new insights into vaccine development.